The work ability index and single-item question: associations with sick leave, symptoms, and health – a prospective study of women on long-term sick leave - Ahlstrom, Linda; Grimby-Ekman, Anna; Hagberg, Mats; Dellve, Lotta (Scandinavian Journal of Work, Environment & Health, 2010)
' ' OBJECTIVES ': 'This study investigated the association between the work ability index (WAI) and the single-item question on work ability among women working in human service organizations (HSO) currently on long-term sick leave. It also examined the association between the WAI and the single-item question in relation to sick leave, symptoms, and health. Predictive values of the WAI, the changed WAI, the single-item question and the changed single-item question were investigated for degree of sick leave, symptoms, and health. ' ' METHODS ': 'This cohort study comprised 324 HSO female workers on long-term (>60 days) sick leave, with follow-ups at 6 and 12 months. Participants responded to questionnaires. Data on work ability, sick leave, health, and symptoms were analyzed with regard to associations and predictability. Spearman correlation and mixed-model analysis were performed for repeated measurements over time. ' ' RESULTS ': 'The study showed a very strong association between the WAI and the single-item question among all participants. Both the WAI and the single-item question showed similar patterns of associations with sick leave, health, and symptoms. The predictive value for the degree of sick leave and health-related quality of life (HRQoL) was strong for both the WAI and the single-item question, and slightly less strong for vitality, neck pain, both self-rated general and mental health, and behavioral and current stress. ' ' CONCLUSION ': 'This study suggests that the single-item question on work ability could be used as a simple indicator for assessing the status and progress of work ability among women on long-term sick leave.
Keywords: cohort study; female; health; long-term sick leave; longitudinal data; prospective study; return to work; sick leave; sickness absence; single-item question; symptom; woman; women; work ability index